2021
DOI: 10.1093/infdis/jiab005
|View full text |Cite
|
Sign up to set email alerts
|

Early Differences in Cytokine Production by Severity of Coronavirus Disease 2019

Abstract: Most patients with coronavirus disease 2019 (COVID-19) experience asymptomatic disease or mild symptoms, but some have critical symptoms requiring intensive care. It is important to determine how patients with asymptomatic or mild COVID-19 react to severe acute respiratory syndrome coronavirus 2 infection and suppress virus spread. Innate immunity is important for evasion from the first virus attack, and it may play an important role in the pathogenesis in these patients. We measured serum cytokine levels in 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 14 publications
11
69
0
Order By: Relevance
“…Likewise, we found increased up-regulation of the IL2 genes in vaccinated relative to unvaccinated macaques. A similar finding has been reported in humans where higher IL 2 levels distinguish mild/asymptomatic forms of COVID-19 disease from the moderate/severe forms [66]. Following viral challenge in our study (specifically, Day 5 to 7), we found down-regulation of IFNα2 genes in BAL cells recovered from vaccinated subjects relative to their unvaccinated controls.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, we found increased up-regulation of the IL2 genes in vaccinated relative to unvaccinated macaques. A similar finding has been reported in humans where higher IL 2 levels distinguish mild/asymptomatic forms of COVID-19 disease from the moderate/severe forms [66]. Following viral challenge in our study (specifically, Day 5 to 7), we found down-regulation of IFNα2 genes in BAL cells recovered from vaccinated subjects relative to their unvaccinated controls.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, we found increased upregulation of the IL2 genes in vaccinated relative to unvaccinated macaques. A similar finding has been reported in humans, where higher IL 2 levels distinguish mild/asymptomatic forms of COVID-19 disease from the moderate/severe forms [ 66 ]. Following viral challenge in our study (specifically, days 5 to 7), we found downregulation of IFNα2 genes in BAL cells recovered from vaccinated subjects relative to unvaccinated controls.…”
Section: Discussionsupporting
confidence: 86%
“…Circulating levels of interleukin-6 (IL-6) are significantly elevated in patients with COVID-19 [ 12 , 26 , 27 ]. The levels of serum IL-6 were found increased in asymptomatic patients as well, although patients with moderate and severe symptoms had much higher elevation in IL-6 levels [ 28 ]. A recent meta-analysis indicates that elevated circulating levels of IL-6 correlate well with increased mortality of COVID-19 patients [ 29 ].…”
Section: Introductionmentioning
confidence: 99%